A New Result of Stability for Thermoelastic-Bresse System of Second Sound Related with Forcing, Delay, and Past History Terms. (24th April 2021) - Ouchenane, Djamel; Khalili, Zineb; Yazid, Fares; Abdalla, Mohamed; Cherif, Bahri Belkacem; Mekawy, Ibrahim
Abstract : We consider a one-dimensional linear thermoelastic Bresse system with delay term, forcing, and infinity history acting on the shear angle displacement. Under an appropriate assumption between the weight of the delay and the weight of the damping, we prove the well-posedness of the problem using the semigroup method, where an asymptotic stability result of global solution is obtained.